The impact of the surfactant Break-Thru® S 301 on the recovery of springtail Folsomia candida juveniles in OECD 232 reproduction test by different extraction methods - Jonas Fischer; Borbala Szabo; Leonid Manikhin; Juliane Filser (PANGAEA, 2025)
The data orginate from lab experiments testing the impact of the surfactant Break-Thru® S 301 on the reproduction and other life history endpoints of the springtail Folsomia candida. The test organisms were exposed for 28 days in three different test soils (sandy, sandy-organic and loamy) and different extraction methods for assessing the number of reproduced juveniles, i.e. heat extraction and flotation. The comparison of these two methods could demonstrate that flotation as the standard extraction method, which is recommended in the most important test guidelines such as OECD 232, produces false-positive effects due to its surface activity in the flotation liquid. Furthermore, a high impact of soil type on the extent of this artefact was proven.